(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
The present article introduces the issue of the cinematic representation of the perfumer’s profession, the so-called “nose” in three selected productions made in the 21st century: Jasminum (2006) by Jan Jakub Kolski, Perfume: The Story of a Murderer (2006) by Tom Tykwer, and Les Parfums (2020) by Grégory Magne. The aim of the analyses and interpretations presented herein was to consider how contemporary cinema portrays perfume creators – both through their specific mythization, as well as through references to the realities of their profession. The introduction to the issue is based on a synthetic overview of the history of the perfumer’s profession, emphasizing elements inherent in it that have, over the ages, linked it with medicine, alchemy, and artistry. The analyses of the images of perfumers in the three selected films enabled the diagnosis of manifestations of mythization through the mystification of J. J. Kolski’s narrative, the hyperbolization – rooted in the thriller convention – of the protagonist’s traits in Perfume, as well as characteristic elements of the contemporary perfume market as conditioning factors of the profession in Les Parfums. The text emphasizes issues of alienation and unique sensory perception of the protagonists, as related to the relationship between the creator, their work, and their surroundings. The analyses also point to the growing importance of the perfumer’s image in popular culture and the significant role of cinema as a medium that brings the secrets of this profession closer to the audience.